American concepts of "green" - Dees, Hilary (Kansas State University, 2011)
According to the Merriam-Webster Online Dictionary (2008) there are ten definitions for the word green as an adjective. The set of definitions that most concerns this paper is the tenth set which states “a: relating to or being an environmentalist political movement, b: concerned with or supporting environmentalism, [and] c: tending to preserve environmental quality (as by being recyclable, biodegradable, or nonpolluting)”. The goal of this paper is to examine each of these three definitions within a linguistic, cultural and historical context. The overall analysis of the definition of green will be done under the theoretical framework of the Sapir-Whorf hypothesis. Linguistic relativity, the change in perception of the world as a result of a change in language, is a key component of this paper; therefore a weak interpretation of the Sapir-Whorf hypothesis is central to the understanding of the breakdown of the concept of green. Another theoretical tenet is Trampe’s (2001) idea of a language-world-system. In the language-world-system, language and world are regarded as mutually interrelated and languages and their environments form open, dynamic systems. This allows for the continuous creation, change and deletion of words and concepts as language follows the cultural system set up by the description of the world around the language users. The final theoretical position essential to this analysis comes from Berman (2001) who asserts “it is through language that we ‘create’ the world we live in-language determines the limits of our world through the creation of categories which act as boundaries.” It is these boundaries, created by language users, that has allowed there to be ten different definitions for one word, which in itself has been subdivided three times. Additional linguistic devices as well as trends of marking and unmarking language with respect to environment will be examined.
Keywords: Green; Language; Environment; Perceptions